(untitled) (Journal of Renal and Hepatic Disorders, 2017)
Since the 1930s when Kimmelstiel and Wilson first described the classic nodular glomerulosclerosis lesions in diabetic kidneys, nephropathy has been recognized as a major and common complication of diabetes. Nearly 40% of diabetics around the world have microalbuminuria, a marker of progression to chronic kidney disease (CKD). Diabetic kidney disease (DKD) is also considered a leading cause of CKD worldwide. Given the significant morbidity, mortality, and health-care burden, several clinical and scientific societies continue to seek a better understanding of this disease. Screening for microalbuminuria and controlling hyperglycemia remain the pillars for the prevention of diabetic nephropathy. However, evidence from multiple studies suggests that controlling DKD is more challenging. Some studies suggest that there is variability in the incidence of renal complications among patients despite comparable hyperglycemic control. Therefore, there has been great interest in studying the inherent, renal protective role of the different antihyperglycemic agents. This review will shed light on the pathophysiology, screening, and diagnosis of DKD. It will also discuss the treatment and prevention of diabetic nephropathy, with a specific focus on comparing the mechanisms, safety profiles, and efficacy of the different antihyperglycemic medications.